Makna Tema Masa Muda dalam MV “Cheers to Youth” SEVENTEEN: Analisis Semiotika Roland Barthes - Safina Raudhotunnisa (Brand Communication, 2026)
This study aims to analyze the meaning of the theme of youth in SEVENTEEN's music video, "Cheers to Youth," using Roland Barthes' semiotic approach. Youth is understood as a transitional phase characterized by emotional growth, identity exploration, and social challenges. This music video was chosen as the object of research because it presents a powerful visual narrative that resonates with the experiences of young people. This analysis applies Barthes's three levels of signification: denotation, connotation, and myth. At the denotative level, visual and audio signs depict the everyday struggles and anxieties of adolescence. Connotation adds cultural and emotional meaning, emphasizing togetherness, self-acceptance, and hope for the future. Meanwhile, the myth that views youth as a precious stage of life that is worth celebrating despite its defenses. These findings highlight how music videos function not only as entertainment but also as a medium of representation, offering insights into the social realities and values held by the younger generation.